Latent Heat Flux (Evapotranspiration) in Summer Season on Rooftop Greening Soil with Bamboo Charcoal Sublayer at a Building in West Japan - Ling Pi; Kaneyuki Nakane (Geofluids)
The effect of a thin and light greening system with bamboo charcoal layer for water retention on heat fluxes, in particular latent heat flux (evapotranspiration rate), under no irrigation condition, on the rooftop of a building in Higashi-Hiroshima, West Japan, was investigated. In April 2019, lawn seeds (Zoysia tenuifolia) were sown which were germinated, reached a height of 70 mm by May when 100% of the vegetation area was covered. The air temperature and humidity at two different heights (0.3 m and 1.8 m) above greening soil surface, latent, and sensible heat fluxes were estimated. Bowen ratio was employed to collect the data on surface heat balance and soil water content during the summer season (June to September) in 2019 on the rooftop of a building in Higashi-Hiroshima, West Japan. The latent heat during daytime for a week without rainfall in each month was compared with the evapotranspiration rate. Owning to the vegetation development, the ground heat flux on greening soil surface decreased from -400 W/m2 to -200 W/m2 (flux from air to soil) during sunny daytime in July, and it was less than -100 W/m2 in August, although net radiation was maintained around 800 W/m2 over the season except in September. The monthly net radiation flux for an entire day (daytime and nighttime) ranged between 55 and 125 W/m2 (average: 95 W/m2) for the summer season of which 32-66% (average: 48%) was occupied by latent heat. Evapotranspiration from greening soil ranged between 1.24 and 1.82 mm/day, averaged at 1.51 mm/day throughout the season, which corresponded to about 26% of total rainfall over the season (r2=0.88, p<0.01; S.E=0.06) between the estimated and measured values. These observations suggested that the thin and bamboo coal light soil layer greening system, even without constant irrigation, could maintain the development of lawn grass and transformed more than half of net radiation to latent heat, i.e., evapotranspiration, insulating most ground heat in midsummer, which may be mostly due to bamboo charcoal sublayer.